1961
DOI: 10.1017/s0003356100033754
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of whole milk with buttermilk in the rearing of calves for veal. 2. Slaughter and carcass composition data

Abstract: 1. Two groups of Friesian calves, one group of 10 reared on whole milk and the other group of 9 changed gradually from whole milk at 21 days of age to a full diet of reconstituted buttermilk powder at 29 days of age, were slaughtered at a live-weight of approximately 203 1b. Data obtained at slaughter showed a highly significantly heavier weight of omental fat from the calves of the whole milk group, and a significant difference in the weight of the unemptied intestinal tract in favour of the buttermilk group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1961
1961
1994
1994

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The mean carcass weights at 12 weeks observed in the 12% and 14% treatments (52-6 and 55-8 kg respectively) compare favourably with the average carcass weight of 59-1 kg recorded by Morgan (1969) for Friesian bull calves reared on greater quantities of milk and slaughtered at 15 weeks. Barton & Kirton (1961), however, observed a mean carcass weight of 53-5 kg from Friesian bull calves reared on whole milk and slaughtered at 8 weeks.…”
Section: Discussionmentioning
confidence: 97%
“…The mean carcass weights at 12 weeks observed in the 12% and 14% treatments (52-6 and 55-8 kg respectively) compare favourably with the average carcass weight of 59-1 kg recorded by Morgan (1969) for Friesian bull calves reared on greater quantities of milk and slaughtered at 15 weeks. Barton & Kirton (1961), however, observed a mean carcass weight of 53-5 kg from Friesian bull calves reared on whole milk and slaughtered at 8 weeks.…”
Section: Discussionmentioning
confidence: 97%
“…Yeates (1964) did not notice any appreciable difference in the proportions of preferred cuts (47-2% vs. 47-2%) between identical twins by creating a difference of 640 lb in live weight from severe restriction of the diet of one. Barton & Kirton (1962) estimated the proportion of muscles in each of seven joints from two groups of Friesian calves fed differently and slaughtered at a live weight of approximately 203 lb. They found slight differences in the proportionate yield of muscular tissue in loin (3-26% vs. 3-61 %) and rib cuts (2-03% vs. 2-20%) between two nutritional treatments without showing any differences in other cuts.…”
Section: Factors Influencing Muscle-weight Distribution •mentioning
confidence: 99%
“…The value of dairy-bred rather than beef-dairy crossbred animals for veal and beef production has been assessed and advocated in New Zealand (Barton & Kirton (1961); Barton (1964aBarton ( , 1966cJoblin (1966)). Studies showed that Friesians grew rapidly and produced acceptable veal or beef.…”
mentioning
confidence: 99%